Single-port Laparoscopic Appendectomy: Beyond the Learning Curve. Issue 5 (October 2018) - Assali, Sarah; Eapen, Sarah; Carman, Terry; Horattas, Sophia; Daigle, Christopher R.; Paranjape, Charudutt
Abstract : Objectives: Previous comparisons between single-port laparoscopic appendectomy (SPLA) and multi-port laparoscopic appendectomy have been conflicting and limited. We compare our single-surgeon, SPLA experience with multi-port cases performed during the same time. Methods: A retrospective chart review of 128 single-surgeon single-port and 941 multi-port laparoscopic appendectomy cases from April 2009 to December 2014 was conducted. Results: Patient demographics and preoperative laboratory values were comparable. SPLA was associated with shorter operative time ( P =0.0001). There was no statistically significant difference in length of hospitalization, postoperative pain medication use, cost, postoperative complication rates (ileus, urinary retention, deep space infection), or readmission between the 2 groups. There were no postoperative incisional hernias in the single-port group. The single-port group had more postoperative oxycodone use ( P =0.0110). Conclusions: Our study supports recently published metaanalyses that fail to support older studies demonstrating longer operative times, and higher hernia rates with SPLA.